Disciplined freedom, branded authenticity, and dependable independence: how tensions enact flexibility in lifestyle blogging careers. Issue 3 (4th May 2018) - Long, Ziyu; Wilhoit, Elizabeth D.
ABSTRACT: Analyzing 219 blog posts from 52 self-employed women lifestyle bloggers in North America, this study shows how these digital professionals navigate tensions and communicatively constitute work flexibility. In their narratives, women bloggers employed tension management approaches such as reframing, continual connections, and reflective practice in response to tensions in enacting temporal–spatial, identity, and financial flexibility. Specifically, women followed oxymoronic constructions – disciplined freedom, branded authenticity, and dependable independence – to embrace and transform competing poles of fluidity↔structure, authenticity↔marketability, and independence↔interconnection. Expanding work–life research to the self-employed digital labor context, this study responds to recent calls to uncover more-than tension management strategies in empirical settings and contributes to a tension-centered, contextual, and processual analysis of workplace flexibility construction.